Transcrição e produção de um catálogo do Livro do Abelionato de Notas do Município de Passo Fundo (1873-1875) - Silva, Ana Vitória Röhrig da (2021)
The transcription of a handwritten document from the 19th century places us in a position of paleographic studies, from start to finish, governed by the Brazilian Document Transcription Standards. Furthermore, building a catalog involves issues of structuring, controlled vocabulary, definitions and redefinitions. The two aspects mentioned, combined in an intervention proposal, establish the theme and objectives of the present work, with a methodology based on Paleography, resulting in more questions and subjects that may give rise to future work. Furthermore, the Passo Fundo society, the interpersonal relationships and established business relationships that can be seen throughout the manuscript and further explored.